KOMUNIKASI INTERPERSONAL ANTARA TOUR GUIDE DAN PENGUNJUNG DALAM MEMBANGUN RASA CINTA KEBUDAYAAN DI PURA MANGKUNEGARAN SOLO - Salim, Muhammad; Sarjono, Herning Suryo; Widiyowati, Estu (Solidaritas, 2024)
Pura Mangkunegaran Solo is one of the cultural heritage sites in Indonesia which has high historical and cultural value. Efforts to preserve culture through education and cultural tourism are one of the focuses of the management of Mangkunegaran Temple. This research aims to analyze interpersonal communication between tour guides and visitors in building a sense of cultural love at Pura Mangkunegaran Solo. The research method used is qualitative with a descriptive approach. The research results show that interpersonal communication between tour guides and visitors at Pura Mangkunegaran Solo plays an important role in building a sense of cultural love. This research also found that there are several factors that influence the quality of interpersonal communication between tour guides and visitors. Tour guides apply several dimensions of communication patterns, including Openness, Trust, Empathy, Caring, Self-Awareness, Clarity, Accuracy, Relevance, Efficiency and Flexibility, to convey information about the history, culture and traditions of Mangkunegaran Temple to visitors.